Application of PAI Learning Based on Higher Order Thinking Skill (HOTS) at SMK Pustek Serpong - Aa Saprudin (Syntax Corporation Indonesia, 2023)
The purpose of Islamic Religious Education is to make people who always improve the quality of their faith and devotion and are able to have noble morals in their lives (Permendikbud RI No. 21 of 2016). This regulation can be understood that in the educational process the emphasis is on character building. The character of students that appears is nothing but the fruit of thinking, for that before student behavior develops so that it becomes a character, the first thing that must be addressed is the mindset of students. This study aims to find out how the learning process based on Higher Order Thinking Skill (HOTS) is carried out at SMK PUSTEK Serpong. This type of research is qualitative research, through this approach researchers see so as to get a clear picture of how PAI learning is carried out at the SMK PUSTEK Serpong institution with research subjects in the form of planning, learning processes to the evaluation stage. Based on the results of the study, it can be concluded that SMK PUSTEK has not fully implemented HOTS-based PAI learning.